2020
DOI: 10.1016/j.ajo.2020.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of New Generation Intraocular Lens Calculation Formulas in Vitrectomized Eyes

Abstract: PURPOSE: To compare the prediction accuracy of new intraocular lens (IOL) calculation formulas (Barrett Universal II [BUII], Emmetropia Verifying Optical [EVO], Kane and Ladas Super formula) and traditional formulas (Haigis, Hoffer Q, Holladay 1, and SRK/T) with Wang-Koch (WK) axial length (AL) adjustment in vitrectomized eyes.DESIGN: Retrospective consecutive case-series study. METHODS: One hundred eleven eyes of 111 patients underwent uneventful phacoemulsification and enVista MX60 implantation after vitrect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…In addition, there were important uncontrolled variables such as the implanted IOL model, which was not the same in all participants of the study. This hyperopic shift in vitrectomized eyes also was reported by Lee et al [68] Recently, another retrospective study published by Tan et al [69] evaluated the refractive results obtained in cataract surgery in vitrectomized eyes by applying next-generation formulas (Barett Universal II, EVO, Kane, and Ladas super formula) against traditional formulas (Haigis, Hoffer Q , Holladay 1, and SRK/T) with Wang-Koch axial length adjustment if required. Before the lens constants were optimized, hyperopic outcomes were noted for all formulas, except for the Kane formula, which revealed no statistically significant bias.…”
Section: Lens Calculation Formulas In Vitrectomized Eyessupporting
confidence: 66%
“…In addition, there were important uncontrolled variables such as the implanted IOL model, which was not the same in all participants of the study. This hyperopic shift in vitrectomized eyes also was reported by Lee et al [68] Recently, another retrospective study published by Tan et al [69] evaluated the refractive results obtained in cataract surgery in vitrectomized eyes by applying next-generation formulas (Barett Universal II, EVO, Kane, and Ladas super formula) against traditional formulas (Haigis, Hoffer Q , Holladay 1, and SRK/T) with Wang-Koch axial length adjustment if required. Before the lens constants were optimized, hyperopic outcomes were noted for all formulas, except for the Kane formula, which revealed no statistically significant bias.…”
Section: Lens Calculation Formulas In Vitrectomized Eyessupporting
confidence: 66%
“…The formulas for IOL selection are all designed for non-vitrectomized eyes. Although some of the new-generation IOL formulas have been demonstrated to be accurate in vitrectomized eyes, 17 this may not be the case with the simpler and more veteran formulas such as the SRK/T. In vitrectomized eyes, the difference in the final effective lens position is likely the result of two factors – the absence of the vitreous, and the possible effect of agents used to fill the vitreous cavity on IOL position.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, analyses have shown that the use of optical biometers with newer fourth generation formulas resulted in no difference in the predictive error or difference between the postoperative and formula-predicted spherical equivalent in eyes that previously had silicone oil tamponade. 30 However, not all eyes are amenable to optical biometry and ultrasound biometry sometimes must be used, usually in the context of very dense lenses or in the presence of vitreous opacities. The AL can be separately measured for each ocular segment, with subsequent velocity conversions as have been previously published.…”
Section: Biometry and Intraocular Lens (Iol) Selectionmentioning
confidence: 99%